Therapeutic approaches for septicemia induced by multidrug-resistant bacteria using desert-adapted plants - Safwat, Nesreen; Elshimy, Rana; Hassanin, Soha O.; El-manakhly, Arwa Ramadan; Noaf, Abdullah N.; Mansour, Abdallah Tageldein; Alshehri, Fatma; Alhomrani, Majid; Alamri, Abdulhakeem S.; Bendary, Mahmoud Mohammed (Frontiers in Cellular and Infection Microbiology, 2025)
AimSepticemia, a life-threatening condition, can arise when bacterial infections are left untreated, allowing the pathogens to spread into the bloodstream. Moreover, infections caused by MDR bacteria are particularly challenging, as they can persist and lead to septicemia even when treated with conventional antibiotics. This study aimed to address this crisis by investigating combination therapies using desert-adapted medicinal plant extracts, including Jasonia candicans (J. candicans), Cistanche tubulosa, Moltkiopsis ciliata, and Thymelea hirsuta, as alternative treatments. The goal was to develop new strategies to combat resistance and improve the management of septic patients.MethodologyIn this study, 400 blood samples from septic patients were analyzed to identify Gram-negative bacterial isolates. Antimicrobial resistance patterns were assessed using standard susceptibility tests. Medicinal plant extracts were evaluated for antimicrobial activity using agar diffusion and broth microdilution assays, while COX-1 and COX-2 inhibition and antioxidant activity were measured using in vitro assays. Histopathological examinations were conducted on treated mice to assess tissue damage and response.ResultsWe observed a high prevalence of E. coli and K. pneumoniae among septic patients. Multidrug resistance was widespread, with many isolates showing high resistance to various antibiotics, although all were susceptible to colistin. Evaluation of desert-adapted plant extracts revealed that J. candicans exhibited the most potent antimicrobial activity and the strongest COX-1 and COX-2 inhibitory activities, as well as antioxidant effects, compared to other extracts and Celecoxib, with a concentration required to achieve 50% enzyme inhibition (IC50) value of 71.97 μg/mL for antioxidant activity. Moreover, the combination of this extract with amikacin showed a synergistic effect, significantly enhancing antimicrobial efficacy and converting over 50% of amikacin-resistant strains to sensitive phenotypes. Histopathological analysis of mice showed that the combination of J. candicans extract and amikacin resulted in reduced severity of pulmonary lesions and splenic damage compared to amikacin alone.ConclusionWe highlighted the potential of J. candicans extracts as combination therapies alongside traditional antibiotics for combating MDR Gram-negative infections, due to their superior antimicrobial, anti-inflammatory, and antioxidant properties.